2016
DOI: 10.1007/s10071-016-1033-y
|View full text |Cite
|
Sign up to set email alerts
|

Mice and rats fail to integrate exogenous timing noise into their time-based decisions

Abstract: Endogenous timing uncertainty results in variability in time-based judgments. In many timing tasks, animals need to incorporate their level of endogenous timing uncertainty into their decisions in order to maximize the reward rate. Although animals have been shown to adopt such optimal behavioral strategies in time-based decisions, whether they can optimize their behavior under exogenous noise is an open question. In this study, we tested mice and rats in a task that required them to space their responses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The current study demonstrated an interval timing deficit in a mouse model of AD and the interpretation of the results within the SET conceptual framework suggested that the observed behavioral phenotype was due to altered consolidation of temporal memories. Future studies are required to evaluate the generalizability of this difference to male 5xFAD mice and to data collected with other timing procedures such as temporal bisection (Akdoğan & Balcı, ; Church & Deluty, ), switch procedure (Balcı, Papachristos, et al, ), and differential reinforcement of low rates of responding (Berkay, Freestone, & Balcı, ; Gür & Balcı, ). Finally, future studies would further inform the validity of our memory processing‐based interpretation of the behavioral results by testing the same mice in behavioral tasks that have revealed a memory phenotype in this model of AD (e.g., novel object recognition, contextual fear conditioning).…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated an interval timing deficit in a mouse model of AD and the interpretation of the results within the SET conceptual framework suggested that the observed behavioral phenotype was due to altered consolidation of temporal memories. Future studies are required to evaluate the generalizability of this difference to male 5xFAD mice and to data collected with other timing procedures such as temporal bisection (Akdoğan & Balcı, ; Church & Deluty, ), switch procedure (Balcı, Papachristos, et al, ), and differential reinforcement of low rates of responding (Berkay, Freestone, & Balcı, ; Gür & Balcı, ). Finally, future studies would further inform the validity of our memory processing‐based interpretation of the behavioral results by testing the same mice in behavioral tasks that have revealed a memory phenotype in this model of AD (e.g., novel object recognition, contextual fear conditioning).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in line with our speculation, the effect of non-scalar (non-representational) sources of variability appears to have stronger manifestation than the scalar sources of representational uncertainty for the shortest target length of Experiment 1. If metric error monitoring (including confidence ratings as a proxy for error magnitude rating) relies primarily on representational scalar uncertainty, the stronger manifestation of non-scalar sources of variability could indeed limit the metric error monitoring performance (for a similar argument in animal decision-making see (Berkay, Freestone, & Balcı, 2016)). Future studies are needed to fully address this possibility.…”
Section: Discussionmentioning
confidence: 99%